The Role of Hospital Image and Patient Satisfaction as Mediation, the Impact of Service Quality on Patient Loyalty - Hamidah, Rifatul; Rokhman, M. Taufiq Noor; Ratnawati, Ratnawati; Kartikasari, Dhian (Asian Journal of Healthcare Analytics, 2025)
The purpose of this study is to investigate how patient satisfaction, loyalty, and the hospital's reputation are affected by service quality at RSSA. The study employs a quantitative approach to achieve its objectives. Data were collected via questionnaires from 94 outpatients at the Pharmacy Service Unit of RSUD Dr. Saiful Anwar who met the inclusion criteria. Data analysis employed the SEM-PLS method. The research findings suggest that service quality does not directly affect patient loyalty. However, both the hospital image and patient satisfaction significantly influence patient loyalty. The mediation analysis indicates that the hospital image does not act as a mediator in the relationship between service quality and patient loyalty. In contrast, patient satisfaction does mediate this effect. This research decisively strengthens hospital management's policies to improve service quality and patient satisfaction, while effectively evaluating the quality of hospital services. This initiative is vital for establishing a strong reputation for the hospital and ensuring unwavering patient loyalty. This research decisively establishes the connection between service quality and customer loyalty.